Rotational isomerization of 3-substituents in synthetic chlorophyll derivatives. Issue 42 (20th October 2016) - Tamiaki, Hitoshi; Mizutani, Keisuke; Sasaki, Shin-ichi; Tatebe, Tomohiro
Abstract: Methyl pyropheophorbides- a possessing a (pseudo)planar substituent at the 3-position were prepared from naturally occurring chlorophyll- a . Some of the semisynthetic π-conjugates with the chlorin skeleton took two atropisomeric conformations for the sterically demanding 3-substituents, CONMe2, NHCOMe, C[CHC(CN)2 ]C(CN)2, and Ph(2, 3, 4, 5-Ph4 ). Their rotational isomerization in a solution was analyzed by 1 H NMR and HPLC. Zinc complex of the 3-aryl-chlorin gave a large energy barrier for the rotation of the C3C3 1 single bond (estimated Δ G ‡ =108 kJ mol −1 at 20 °C) and the atropisomerically pure conformers were separated at room temperature. Graphical abstract: